Formative computer-based assessments to enhance teaching and learning - Noleen Leach, Noleen Leach (South African Journal of Higher Education, 2016)
Formative assessments have the potential to benefit student learning and enhance teaching, as their feedback can both assist students to assess the quality of their work, and assist university teachers to understand students’ strengths and weaknesses. This paper reports on part of a broader exploratory study, which involved 360 undergraduate law students at a university in South Africa. Weekly formative computer-based assessments were introduced prior to lectures for a period of eight weeks. This intervention could be understood as a variant of formative assessment, which is described by Carless (2007, 171) as “pre-emptive assessment”. A survey was conducted among students and lecturers at the end of the pre-emptive formative assessment intervention. This study found strong support for these formative assessments among students, as well as lecturers, and shows a high participation rate in the assessments among students. The study further challenges Biggs’ (1989, 7) four-step model of constructive alignment with regard to the role of formative assessment that can precede teaching activities. Hence, it proposes an adaptation of that model.